2016
DOI: 10.1074/jbc.m115.692871
|View full text |Cite
|
Sign up to set email alerts
|

Two Degradation Pathways of the p35 Cdk5 (Cyclin-dependent Kinase) Activation Subunit, Dependent and Independent of Ubiquitination

Abstract: Cdk5 is a versatile protein kinase that is involved in various neuronal activities, such as the migration of newborn neurons, neurite outgrowth, synaptic regulation, and neurodegenerative diseases. Cdk5 requires the p35 regulatory subunit for activation. Because Cdk5 is more abundantly expressed in neurons compared with p35, the p35 protein levels determine the kinase activity of Cdk5. p35 is a protein with a short half-life that is degraded by proteasomes. Although ubiquitination of p35 has been previously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…1E,F). Because p35 has a short half-life (Patrick et al, 1998), and its abundance in the synapse is controlled mainly by ubiquitindependent and -independent degradation pathways (Takasugi et al, 2016), and to a lesser extent by local protein synthesis (Patrick et al, 1998;Shah and Lahiri, 2014), we postulated that the rapid effect of tPA on p35 expression is due to inhibition of its degradation. To test this hypothesis, we first studied the effect of protein synthesis inhibition on the abundance of p35.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1E,F). Because p35 has a short half-life (Patrick et al, 1998), and its abundance in the synapse is controlled mainly by ubiquitindependent and -independent degradation pathways (Takasugi et al, 2016), and to a lesser extent by local protein synthesis (Patrick et al, 1998;Shah and Lahiri, 2014), we postulated that the rapid effect of tPA on p35 expression is due to inhibition of its degradation. To test this hypothesis, we first studied the effect of protein synthesis inhibition on the abundance of p35.…”
Section: Resultsmentioning
confidence: 99%
“…p35 is regulated transcriptionally by multiple factors, including nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF) and tumor necrosis factor-alpha (TNFα) (Harada et al, 2001;Utreras et al, 2009); and postranscriptionally by several microRNAs (Moncini et al, 2017). Furthermore, its degradation is mediated by ubiquitin-dependent and -independent pathways (Takasugi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research revealed that P35 degradation occurs by both ubiquitin-dependent and ubiquitin-independent pathways. P35 degradation leads to the inhibition of P25 expression, which could over-activate CDK5 to induce neuronal cell death [ 27 ]. Various experiments demonstrated the significant role of CDK5 in the CNS by broadly disrupting in neuronal layering of various brain structures, such as the cerebral cortex, cerebellum, hippocampus and olfactory bulb [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Cyclin-dependent kinase 5 was first recognized as a neuron-specific CDK due to the majority distribution of CDK5 activators residing within neurons. 16 However, emerging evidence shows CDK5 might have additional roles in gene expression, cell migration, apoptosis, and pathological processes, leading to inflammation, diabetes, immune dysfunction, and cancer [17][18][19][20][21][22] (Table 1).…”
Section: Introductionmentioning
confidence: 99%